ASSESSMENT FOR LEARNING IN PHYSICAL EDUCATION AND SPORT LESSONS (University Arena, 2024)
The study focuses on clarifying the terms and purposes of assessment for learning in Physical Education and Sport lessons andhow we can use them to support the progress of our students, provides examples of different types of assessment for learning inphysical education and explains why teachers should include them as part of their instruction.This article describes the most used forms of assessment in physical education and emphasizes the importance of using them inboth physical activity and physical fitness for promoting physical activity. Effective evaluation practices are needed to optimize theeffectiveness of physical education programming. Assessment for learning is an essential part of education as it defines whet her ornot the objectives of teaching are being met, assessment affects decisions about grades and educational needs of students.Assessment for learning involves using it, as part of teaching and learning, in ways that will raise the student`s achievement.Assessments are the tool that physical educators use to measure the skills and fitness levels their students learn and achieve in thePhysical Education class. They help to show yourself and others that your students are learning and becoming more physically fitas a result of being in your class. Assessment is very important in Physical Education as it provides information on strengths,weaknesses and educational requirements, it gives students the opportunity to demonstrate what they know and are capable to d o, determines student progress and motivates them to improve their performance, informs future planning and teaching and judges which aspects of teaching have been effective or inefficient.Student assessment is “the gathering of evidence about student achievement and making interferences about student progressbased on the evidence”. Physical Education teachers collect and track assessment data to make decisions about instruction and tomeasure student learning continually throughout the learning sequence (SHAPE America, 2014).
Keywords: assessment for learning; physical education and sport; student assessment